Feasibility of Coping Effectiveness Training for Caregivers of Children with Autism Spectrum Disorder: a Genetic Counseling Intervention. Issue 1 (6th September 2017) - Haakonsen Smith, Christy; Turbitt, Erin; Muschelli, John; Leonard, Lori; Lewis, Katie L.; Freedman, Brian; Muratori, Michelle; Biesecker, Barbara B.
Abstract: Caregivers of children with autism spectrum disorder (ASD) may find it difficult to feel a sense of control and to cope with the overall physical and emotional demands of caring for their child. While caregivers are able to successfully cope with a high level of stress, there are limits to their resources and abilities to cope over time. Genetic counselors working with affected families may be able to help parents more effectively manage stress related to the disorder. Few short‐term interventions have been reported in genetic counseling yet implementation of evidence‐based examples may be achievable. This study aimed to assess the feasibility of a coping effectiveness training (CET) intervention designed to enhance coping self‐efficacy (CSE) among caregivers of children with ASD, with the eventual goal of translating this intervention into genetic counseling practice. A randomized treatment‐control design was used to investigate the feasibility of an intervention using CET among caregivers of children with ASD. The primary outcome was the feasibility of the intervention; the secondary outcome was improvements in CSE in the intervention group as compared to the control group. Caregivers were recruited and randomized into the treatment (n=15) or control (n=13) groups. Of these, 22 completed the study (retention: 78.6%). The intervention was highly feasible; most caregivers found the CET helpful, practical, useful, and relatively easy to attend. The treatment group demonstrated significantly increased CSE from pre‐intervention to post‐intervention (p=0.02). Between group differences were not significant when comparing the pre‐post changes. We provide preliminary evidence that CET may be beneficial to caregivers of children with ASD. The results of this feasibility study support development of a phase II study of this intervention in a larger cohort, aimed to be implemented into a genetic counseling setting.